ANALISIS PENGARUH KOMITMEN ORGANISASI DAN NILAI ETIK PERUSAHAAN TERHADAP INTENSI TINDAKAN WHISTLEBLOWING - Laura F BR Sihaloho; Wahyu Meiranto (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the relationship of organizational commitment, corporate ethical values on the intention of whistleblowing internally and externally on Government Banking in the City of Semarang. This study uses four variables which are divided into dependent variables consisting of intentions of whistleblowing internally and externally, independent variables consisting of organizational commitment and corporate ethical values as well as demographic variables that act as covariant variables. Research data is primary data with survey questionnaire methods obtained through respondents. The questionnaire was distributed to 80 government banking accountants in Semarang based on convenience sampling for sample selection. Research uses the theory of planned behavior and social exchange theory. The study has four hypotheses which were tested using multiple regression analysis. The statistical results of this study indicate that organizational commitment has a positive relationship to the intentions of internal whistleblowing, corporate ethical values have a negative relationship to the intentions of external whistleblowing. While organizational commitment does not affect the intention of external whistleblowing, corporate ethical values have no effect on the intentions of internal whistleblowing.